ASPEK KEUANGAN YANG MEMPENGARUHI KINERJA PERUSAHAAN MENGGUNAKAN NILAI PASAR TOBIN’S Q - Sumarna, Alfonsa Dian; Yuliani, Nur Fitria (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2021)
The working capital is an important evalution for calculating company performance which indirectly influence the Indonesia’s trade balance. This study aims to examine the influence of working capital on the performance before (2016-2017) and after (2018-2019) trade balance defisit. Working capital consists of Receivable Collection Period, Inventory Conversion Period, Payable Deferral Period, and Cash Conversion Cycle, while liquidity proxied by Current Ratio. Company performance is proxied by the company value using Tobin’s Q. This study using purposive sampling of manufacturing companies sub-sector consumer goods industry that are listed in Indonesian Stock Exchange which fulfill the criterias with total observation are 106 samples. Data analysis using Eviews9. The hypothesis tests using t-test and F-test. The finding is working capital and liquidity before defisit period have significant influence to company performance except Receivable Collection Period. Meanwhile after defisit period working capital and liquidity have significant influence to company performance except Receivable Collection Period and Payable Deferral Period. The result for both period is significant influence simultaneously.